PENGARUH BIMBINGAN BELAJAR ONLINE TERHADAP PRESTASI BELAJAR SISWA SELAMA PEMBELAJARAN TATAP MUKA TERBATAS DI SMA NEGERI 1 UJUNGBATU - Despra Melly; Rr. Sri Kartikowati; Fima Alia Sari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article investigates the low learning outcomes in Economics for the XI IPS class of SMA Negeri 1 Ujungbatu during limited face-to-face learning. The research employed a quantitative descriptive method to examine the effect of online courses on students’ learning achievement. The population consisted of 30 students who participated in online learning through Ruangguru. Data were collected using questionnaires for online course usage and documentation for students’ Economics scores in the odd semester of the 2021/2022 academic year. Data analysis was conducted using descriptive statistics and simple linear regression through SPSS, following classical assumption tests. The results indicate that online courses have a positive and significant effect on students’ learning achievement, with a regression coefficient of 0.428 and a contribution of 20.8%. These findings suggest that online courses can serve as an effective alternative to enhance students’ learning outcomes during limited face-to-face learning.